The interpretation dispute in literary studies – not as radical as it is painted - Krzysztof Tarkowski (Przestrzenie Teorii, 2018)
This review of Tomasz Szymon Markiewka’s book, entitled Interpretation Argument in Literary Studies. Analysis of Selected Theoretical Conceptions of 20th Century, focuses on reconstruction of its main theses, as well as on evaluate their methodological aspects. The first part deals with theoretical issues, mainly of terminological decisions and relation between the literature studies and philosophy. Next, article assesses the pros and cons of the main part of the book, which contains analysis of five selected theorists’ ideas of interpretation. The final part of the review raises the issue of the method of interpretation literary texts.